Effect of digestive enzymes on the activity of camel‐milk insulin. (9th January 2020) - Abou‐Soliman, Nagwa H I; Awad, Sameh; Desouky, Marwa Mohamed
Abstract : This study investigated the effect of digestive enzymes on the activity of camel‐milk insulin. The digestion was performed using the sequential action of pepsin and pancreatin. Proteolysis degree was estimated using the O ‐phthaldialdehyde method. Insulin concentration was determined using an enzyme‐linked immunosorbent assay (ELISA). Results revealed that milk proteins were partially digested by pepsin alone and the degradation was increased during the pepsin–pancreatin digestion as compared to control. Insulin lost its activity after 30 min of pepsin digestion, and it was not detected by ELISA. This study strongly suggests that insulin is not responsible for the antidiabetic action of camel's milk.